Problems of Online Learning during Covid-19 Pandemic in Speaking For Professional Context Class - Sri Ariani; Tawali Tawali (Universitas Pendidikan Mandalika, 2021)
Indonesia's Government has made policy in the education sector due to the COVID-19 pandemic situation. Previously teaching and learning process especially in the higher institution is held face to face, and it switches to fully online learning. This situation forces the lecturer and students to adopt online learning and effected to their learning experiences. This current study is aimed at analyzing the students’ difficulties during online learning in speaking for professional context subject during COVID-19 situation. This research was held using a descriptive qualitative method approach. The data was obtained from an online questionnaire and interview conducted to 45 students of the second semester of the English Department who joining speaking for professional context class at Universitas Pendidikan Mandalika in Mataram, West Nusa Tenggara, Indonesia. The findings of the research revealed various problems for students as indicated in the current research. A total of 5 problems arose during online learning in the Speaking for Professional class. The arisen problem was: The first problem was related to Youtube video as the source of learning materials. The second problem was dealing with the students’ difficulties in elaborating the materials given by the lecturer during an online class. The third problem was related to the students’ procedure in doing the project or assignment given by the lecturer. The fourth problem was dealing with Students’ limitations in accessing ZOOM Meetings. The Students’ learning equipment and supporting facilities also contributed as the fifth arisen problems of the students while having online learning during COVID-19 pandemic situations. The findings provide information for further development and improvement in online teaching and learning procedures. Further research on the strategy of how the students face the challenge and adapt are encouraged.